Arterial grafts exhibiting unprecedented cellular infiltration and remodeling in vivo: The role of cells in the vascular wall. (May 2015) - Row, Sindhu; Peng, Haofan; Schlaich, Evan M.; Koenigsknecht, Carmon; Andreadis, Stelios T.; Swartz, Daniel D.
Abstract: Objective: To engineer and implant vascular grafts in the arterial circulation of a pre-clinical animal model and assess the role of donor medial cells in graft remodeling and function. Approach and results: Vascular grafts were engineered using Small Intestinal Submucosa (SIS)-fibrin hybrid scaffold and implanted interpositionally into the arterial circulation of an ovine model. We sought to demonstrate implantability of SIS-Fibrin based grafts; examine the remodeling; and determine whether the presence of vascular cells in the medial wall was necessary for cellular infiltration from the host and successful remodeling of the implants. We observed no occlusions or anastomotic complications in 18 animals that received these grafts. Notably, the grafts exhibited unprecedented levels of host cell infiltration that was not limited to the anastomotic sites but occurred through the lumen as well as the extramural side, leading to uniform cell distribution. Incoming cells remodeled the extracellular matrix and matured into functional smooth muscle cells as evidenced by expression of myogenic markers and development of vascular reactivity. Interestingly, tracking the donor cells revealed that their presence was beneficial but not necessary for successful grafting. Indeed, the proliferation rate and number of donor cells decreased over time as the vascular wall was dominated by host cells leading to significant remodeling and development of contractile function. Conclusions: These results demonstrate that SIS-Fibrin grafts can be successfully implanted into the arterial circulation of a clinically relevant animal model, improve our understanding of vascular graft remodeling and raise the possibility of engineering mural cell-free arterial grafts.